The German specific emotion concept SEHNSUCHT and its equivalents in English-speaking cultures - Mizin, Kostiantyn (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2024)
The aim of the proposed article is to develop a technique that can be used to identify those emotion concepts (ECs) in the target cultures that most adequately convey the idea of fragments of the emotional world of representatives of the source cultures presented in specific concepts. The technique is tested on the example of the German specific EC sehnsucht, and the target culture is such a collective notion as “English-speaking cultures”, since there is no such concept in the English-speaking environment. Based on the definition analysis of the name of the EC sehnsucht – the lexeme Sehnsucht – its closest correspondences in English – longing, yearning, pining, craving, desire and wistfulness – have been identified. The disclosure of all semantic facets of the EC sehnsucht made it possible to “weed out” the ECs wistfulness, desire, craving and pining as those that demonstrate a lower level of equivalence compared to longing and yearning, which are the closest to sehnsucht in terms of content. The analysis of the frequency indices of conceptual proximates of the ECs sehnsucht, longing and yearning has revealed that in the pairs sehnsucht – longing and sehnsucht – yearning the similarity of semantic structures is 70 %, which indicates a rather high level of equivalence of these pairs. The comparison of the average values of the evaluation and intensity indicators of these three ECs revealed that longing and yearning represent more positive emotional experiences than sehnsucht. Mostly it concerns the EC yearning, which is both more positive and more intense. Therefore, it is longing that can be considered the EC in the English-speaking cultures and within their representatives that can evoke the most adequate idea of the emotional experience represented by the German EC sehnsucht.